Pregnancy after Cancer Treatment and Pregnancy Associated Cancer: A Single Center Experience with 96 Cases - Mert Turğal; Kemal Beksaç; Derman Başaran; Aslıhan Yazıcıoğlu; Özgür Özyüncü; Ömer Aran; M. Sinan Beksaç (Medical Network, 2016)
OBJECTIVE: The objective of our study was to evaluate our experience on pregnancies after cancer treatment and pregnancy-associated cancer. STUDY DESIGN: The clinical records of 96 pregnant women including previously received treatment for cancer and association of cancer with pregnancy who admitted to our department were enrolled between 2002 and 2012. Demographics, pregnancy outcomes, maternal and fetal complications, perinatal outcomes, cancer types and treatments performed were evaluated. RESULTS: The study group was consisting of 96 cases, 59 out of 96 were cancer survivors and 37 were pregnancy-associated cancer patients. Of those thirty seven, 25 were synchronous with the pregnancy and 12 were metachronic. Pregnancies resulted in 77 healthy newborns, 7 abortions and 12 medical terminations. The most common type of cancer was the breast cancer in 25 patients, followed by thyroid, leukemia, osteosarcoma, lymphoma and ovarian cancer. Patients were treated for their cancer with different modalities including surgery, chemotherapy and radiotherapy. We encountered maternal mortality in 8 cases, all occurred after delivery. CONCLUSIONS: Since management of a pregnancy of a cancer survivor and pregnant woman with cancer a hard work, multidisciplinary approach involving gynecologists, pediatricians, oncologists is essential. Interval between cancer and pregnancy and timing of initiation of therapy in cases of pregnancy associated cancer are important issues in the perspective of fetal/neonatal well-being.